2015
DOI: 10.3892/etm.2015.2841
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural identification of telocytes in the muscularis of chicken ileum

Abstract: Abstract. Telocytes (TCs) are a specialized type of interstitial cells, characterized by a small cell body and long, thin processes, that have recently been identified in various cavitary and non-cavitary organs of humans and laboratory mammals. Chickens present significant economical and scientific notability; however, ultrastructural identification of TCs remains unclear in birds. The aim of the present study was to describe electron microscopic evidence for the presence of TCs in the chicken gut. The ileum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…TCs are identified in a wide variety of organs from diverse species including mammals 8 11 , avian 12 , 13 , reptiles 14 , Amphibians 15 and aquatic species 16 , 17 and parasitic worm 18 . They are located in the trachea and lungs 19 , heart 20 and the blood vessels 21 , kidney, ureter, urinary bladder 22 , tongue 23 , oesophagus, stomach and small and large intestines 24 , liver , pancreas 14 , testis 25 , prostate 26 , efferent ductules 27 ovaries, oviducts, uterus, vagina, mammary glands and placenta 26 , spleen 8 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…TCs are identified in a wide variety of organs from diverse species including mammals 8 11 , avian 12 , 13 , reptiles 14 , Amphibians 15 and aquatic species 16 , 17 and parasitic worm 18 . They are located in the trachea and lungs 19 , heart 20 and the blood vessels 21 , kidney, ureter, urinary bladder 22 , tongue 23 , oesophagus, stomach and small and large intestines 24 , liver , pancreas 14 , testis 25 , prostate 26 , efferent ductules 27 ovaries, oviducts, uterus, vagina, mammary glands and placenta 26 , spleen 8 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Telocytes have also been detected by electron microscopy in tissues of various reptile species, including the male and female reproductive systems of the Chinese softshell turtle (Pelodiscus sinensis) (Ullah et al 2014;Yang et al 2015a) and in the pancreas and gastric mucosa of the Chinese giant salamander (Andrias davidianus) (Zhang et al 2016a, b). Telocytes are also located in the walls of the gut and uterine tubes of some bird species (Yang et al 2015b;Yang et al 2017). Telocytes in mammals have also been intensely studied.…”
Section: Question 4 Are Telocytes Described Exclusively In Humans?mentioning
confidence: 99%
“…Presumably, this support might contribute to tissue homeostasis, regeneration or repair and transmission of intercellular signals . Ultrastructural evidence showed that telocytes were spatially close not only to capillaries, nerve fibres, myocytes, smooth muscle cells and stem cells but also to macrophages, mast cells, eosinophils and lymphocytes . Telocytes might modulate the immunocytes through direct synapse‐like contact or indirect paracrine communication by secreting soluble mediators, such as IL‐6, VEGF and nitric oxide .…”
Section: Introductionmentioning
confidence: 99%